(untitled) (Research, Society and Development, 2023)
The study aimed to identify the collaboration of adapted physical education and the development of its possible contributions to the motor improvement of children with Autistic Spectrum Disorder (ASD). A systematic review was carried out with complete articles and dissertations published between the period 2017 to 2021 in the electronic databases Pubmed, Scielo, Lilacs. Initially, 63 articles were identified. After reading the titles of the documents, 25 articles were selected. And after reading the abstracts, only 10 were considered eligible who fully met the inclusion criteria. The articles indicated the practice of sports, balance and psychomotricity, motor practices with trampolines and outdoor activities, aquatic activities and muscle strengthening exercises. The interventions used showed a decrease in stereotyped behaviors, an improvement in the development of motor coordination and postural control, a decrease in sensory dysregulation and an increase in the motor repertoire. It is concluded that physical education linked contribute to the cognitive and motor development of children with ASD through a specifically designed exercise program.